Título Padrão - Getter, Russel (Revista de Ciências Sociais, 2019)
The purpose of this paper is to test the proposition that government is the most important single agent responsible for increases in leveis of economic development in the African States. The States are diverse with respect to political institutions, culture, and economic and social structure. They are similar, however, in that all the states can be considered potential or actual modernizers, almost ali share a colonial heritage, and ali are most appropriately in the "new nation" category in terms of outlook and aspiration. Moreover, economic development, unlike political or social development ,is the common denominator by which developlng nations compare themselves to thetr neighbors and project a national image to the larger world community. Therefore, the States of Africa provide an ideal background for e:z:amining the relationship between governmental activlty and economic development in the developing areas, whithout regard for the Tarious types or kinds ot political and social systems.